Farrerol inhibits ferroptosis and protects against LPS-induced acute lung injury by targeting the RUNX1/SLC7A11 axis - Yang, Yueyan; Deng, Shihua; Liu, Teng; Yin, Qing; Yang, Min; Zhang, Xintao; Jiang, Zhongyong; Wang, Xiaobian; Zhang, Sunhan; Zhang, Ting; Wu, Dongming; Xu, Ying (Frontiers in Immunology, 2026)
IntroductionAcute lung injury (ALI) is a critical condition with diverse etiologies, characterized by high mortality rates and a lack of specific therapeutic interventions. Farrerol, a naturally occurring flavonoid isolated from Rhododendron spp., exhibits potent anti-inflammatory and antioxidant activities. Previous studies have indicated that farrerol exerts protective effects against lipopolysaccharide (LPS)-induced ALI; however, the underlying mechanisms remain elusive. This study aimed to elucidate the protective mechanisms of farrerol against LPS-induced ALI.MethodsWe evaluated the efficacy of farrerol using both in vitro (LPS-stimulated BEAS-2B cells) and in vivo (LPS-induced ALI in mice) models. The protective mechanism of rhododendron against ALI was investigated using proteomics, cellular thermal shift assays, co-immunoprecipitation, and molecular docking.ResultsPretreatment with farrerol significantly improved cell viability and reduced lactate dehydrogenase release in LPS-induced BEAS-2B cells. In vivo, farrerol effectively alleviated LPS−induced pulmonary edema and histopathological damage in mice. Mechanistically, we found that farrerol directly binds to and stabilizes runt-related transcription factor 1 (RUNX1), thereby transcriptionally activating the expression of solute carrier family 7 member 11. Overexpression of RUNX1 mimicked the protective effects of farrerol, while knockdown of RUNX1 abolished these effects.DiscussionFarrerol could directly bind and stabilize the expression of RUNX1, thereby enhancing SLC7A11 transcription and ultimately inhibiting ferroptosis. Thus, farrerol is a potential therapeutic agent for ALI.